Leukemia Cutis in a 32-Year-Old Male with Acute Myeloid Leukemia (Journal of Enam Medical College, 2019)
Leukemia cutis (LC) is a rare cutaneous manifestation of leukemia. Clinical presentation of the disease differs among patients depending on types. LC can precede, follow, occur simultaneously with, or present in the absence of the systemic leukemia. Leukemic involvement of the skin may appear as initial manifestation of recurrence or dissemination of systemic disease. Here we report a case of a 32-year-old male patient known to have acute myeloid leukemia with multiple cutaneous lesions diagnosed as LC.J Enam Med Col 2019; 9(2): 133-135